Diagnostic and Therapeutic Approaches in Lung Cancer: A Single Institution Experience on 96 Patients - Dubus, Turkan; Akpolat, Bektas; Uzman, Ozlem; Demıryontar, Dilay; Toker, Nil (Fırat University, 2014)
Objective: To analyze the diagnostic and therapeutic approaches in lung cancer patients treated at a single institution. Material and Method: Ninety six patients with histopathologically verified lung cancer diagnosed between 2007 and 2010 were retrospectively analyzed with respect to clinical, radiological and bronchoscopic findings. Results: Male/Female ratio was 87/9, median age was 59 (45-74). Eighty two (85.4%) patients were smokers. The most frequent clinical findings were cough in 89.5%(n= 86), weight loss in 77.1%(n= 74), and phlegm in 70.8% (n= 68) of the patients. The most common findings on chest X-rays were mass in 93.7% (n= 90), mediastinal enlargement in 56.2%(n= 54), and atelectasis in 54.2%(n= 52). Histologic subtypes of the tumors were small cell lung cancers (SCLC) in 6 (6.3%), and non small cell lung cancers (NSCLC) in 90 (93.7%). Bronchoscopic and radiologic examinations revealed that the primary tumor was located in the left lung in 56 patients (58.3%). During bronchoscopy the tumoral lesions were evaluated as endobronchial in 56.2% (n= 54) and submucosal in 27.1% (n=26). The two diagnostic biopsy methods were fiberoptic bronchoscopy (FOB) and transthoracic needle biopsy (TTNB), their rates were 83.3% and 16.7% respectively. Based on the stage, SCLC patients were defined as limited in 2 patients (2.1%) and extensive stage in 4 (4.1%). NSCLC were considered operable in 41 (42.7%) patients and inoperable in 49 (51.0%). Metastases were detected in 25 patients (26.0%). Conclusion: In this study we aimed to emphasize that lung cancer operations do not necessarily require specialized centers, and in patients suitable for surgery all types of lung cancer operations can be performed successfully in any state hospital staffed by a single or a few specialists, with very low morbidity and mortality rates.

Amaç: Tek bir merkezde tedavi edilmiş olan akciğer kanserli hastalarda tanısal ve terapötik yaklaşımları incelemek. Gereç ve Yöntem: 2007-2010 yılları arasında klinik, radyolojik ve bronkoskopik bulgulara göre patolojik tanısı konulan 96 hasta retrospektif olarak değerlendirildi. Bulgular: Erkek/Kadın: 87/9, ortanca yaş: 59 (45-74). 82 hasta (%85.4), sigara kullanıcısı idi. Hastaların çoğunda klinik bulgu olarak, öksürük (n= 86) %89.5, kilo kaybı (n= 74) %77.1, balgam (n= 68) %70.8 görüldü. Akciğer grafisinde en sık tespit edilen bulgular kitle (n= 90) %93.7, mediastinal genişleme (n= 54) %56.2, atelektazi (n= 52) %54.2 idi.. 96 hastanın histolojik alt tipleri küçük hücreli akciğer kanseri (KHAK) (n= 6) %6.3, küçük hücreli dışı akciğer kanserleri (KHDAK) (n= 90) %93.7 idi. Bronkoskopik ve radyolojik incelemelerde primer tümörün sol akciğerde (n= 56) %58.3 daha sık olduğu görüldü. Bronkoskopi yapılan olgulardan 54'ü (%56.2) endobronşiyal, 26'sı (%27.1) submukozal tutulum olarak değerlendirildi. En sık tanı metodları fiberoptik bronkoskopi (FOB) (%83.3) ve transtorasik iğne biyopsisi (TTİB) (%16.7) idi. Evrelerine göre KHAK'de 2'si (%2.1) sınırlı evre, 4'ü (%4.1) ileri evre; KHDAK olgularından 41'i (%42.7) operable, 49'u (%51.0) inoperabl olarak değerlendirildi. Hastalarımızın 25''inde (%26.0) uzak organ metastazı saptandı. Sonuç: Bu çalışmayla akciğer kanseri cerrahisinin mutlaka belli merkezlerde yapılmasının şart olmadığını, bugün artık tek hekimin veya bir kaç hekimin çalıştığı herhangi bir devlet hastanesinde de ameliyata uygunluğu olan her türlü akciğer kanseri ameliyatının çok düşük morbidite ve mortalite oranlarıyla başarılı bir şekilde yapılabildiğini vurgulamak istedik.
Akciğer Kanserinde Tanı ve Tedavi Yaklaşımları: 96 Hasta Üzerinde Tek Kurum Deneyimi